Monocyte-derived peritoneal macrophages protect C57BL/6 mice against surgery-induced adhesions - Sahputra, Rinal; Dejyong, Krittee; Woolf, Adrian S.; Mack, Matthias; Allen, Judith E.; Rückerl, Dominik; Herrick, Sarah E. (Frontiers in Immunology, 2022)
Peritoneal adhesions commonly occur after abdominal or pelvic surgery. These scars join internal organs to each other or to the cavity wall and can present with abdominal or pelvic pain, and bowel obstruction or female infertility. The mechanisms underlying adhesion formation remain unclear and thus, effective treatments are not forthcoming. Peritoneal macrophages accumulate after surgery and previous studies have attributed either pro- or anti-scarring properties to these cells. We propose that there are complex and nuanced responses after surgery with respect to both resident and also monocyte-derived peritoneal macrophage subpopulations. Moreover, we contend that differences in responses of specific macrophage subpopulations in part explain the risk of developing peritoneal scars. We characterized alterations in peritoneal macrophage subpopulations after surgery-induced injury using two strains of mice, BALB/c and C57BL/6, with known differences in macrophage response post-infection. At 14 days post-surgery, BALB/c mice displayed more adhesions compared with C57BL/6 mice. This increase in scarring correlated with a lower influx of monocyte-derived macrophages at day 3 post-surgery. Moreover, BALB/c mice showed distinct macrophage repopulation dynamics after surgery. To confirm a role for monocyte-derived macrophages, we used Ccr2-deficient mice as well as antibody-mediated depletion of CCR2 expressing cells during initial stages of adhesion formation. Both Ccr2-deficient and CCR2-depleted mice showed a significant increase in adhesion formation associated with the loss of peritoneal monocyte influx. These findings revealed an important protective role for monocyte-derived cells in reducing adhesion formation after surgery.